Effects of Phyllanthus amarus and Euphorbia hirta Dip Treatments on the Protection of Striped Catfish (Pangasianodon hypophthalmus) Fillets against Spoilage during Ice Storage. Issue 10 (26th November 2021) - Le Anh Dao, Nguyen; Phu, Tran Minh; Douny, Caroline; Quetin-Leclercq, Joëlle; Hue, Bui Thi Buu; Bach, Le Thi; Quynh Nhu, Truong; Thi Bich Hang, Bui; Thi Thanh Huong, Do; Thanh Phuong, Nguyen; Kestemont, Patrick; Scippo, Marie-Louise
ABSTRACT: This study was conducted to evaluate the effects of herbal extracts on the quality of striped catfish ( Pangasianodon hypophthalmus ) fillets throughout the storage period. Quality changes during ice storage of striped catfish fillets were studied after dip treatments in aqueous solutions of ethanolic extract of Phyllanthus amarus (0.02% and 0.04%, w/v) or Euphorbia hirta (0.06% and 0.02%, w/v). The control (dipped in tap water) and the treated fish samples were analyzed periodically for total viable counts (TVC), peroxide value, physicochemical parameters (pH, texture), and sensory properties. Results indicated that Pseudomonas spp. and Listeria monocytogenes were absent in the raw fish fillets, reflecting the safety of raw materials regarding specific spoilage and psychrotrophic pathogenic microorganisms. Fish fillets dipped in 0.04% P. amarus extract solution displayed lower TVC values (4.76 log10 CFU/g) during the initial storage period compared to treatment with E. hirta extracts. Dip treatments in water containing P. amarus or E. hirta extracts significantly reduced the primary lipid oxidation in fish samples. In conclusion, the dip treatment in water containing 0.04% P. amarus or 0.06% E. hirta extract was effective to maintain a good sensory quality of the fish fillets and to prolong their shelf life up to 8 days under ice storage.